2014
DOI: 10.1093/mnras/stu1334
|View full text |Cite
|
Sign up to set email alerts
|

Black hole-like hysteresis and accretion states in neutron star low-mass X-ray binaries

Abstract: We have systematically studied a large sample of the neutron star low mass X-ray binaries (LMXBs) monitored by the Rossi X-ray Timing Explorer (50 sources; 10000+ observations). We find that the hysteresis patterns between Compton dominated and thermal dominated states, typically observed in black hole LMXBs, are also common in neutron star systems. These patterns, which also sample intermediate states, are found when looking at the evolution of both X-ray colour and fast variability of ten systems accreting b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
139
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 142 publications
(155 citation statements)
references
References 75 publications
(77 reference statements)
16
139
0
Order By: Relevance
“…Comparing the state classification defined by Muñoz-Darias et al (2014) and the X-ray colour analysis reported by Kajava et al (2014) for 4U 1636-536, 4U 1608-52, and 4U 1728-34, we found that for a few bursts the two methods resulted in ambiguous classifications (particularly for 4U 1636-536), and in those cases we adjusted the limits so that both colour and rms diagrams had the least ambiguities. We also find that (see Fig.…”
Section: Muñozmentioning
confidence: 88%
See 1 more Smart Citation
“…Comparing the state classification defined by Muñoz-Darias et al (2014) and the X-ray colour analysis reported by Kajava et al (2014) for 4U 1636-536, 4U 1608-52, and 4U 1728-34, we found that for a few bursts the two methods resulted in ambiguous classifications (particularly for 4U 1636-536), and in those cases we adjusted the limits so that both colour and rms diagrams had the least ambiguities. We also find that (see Fig.…”
Section: Muñozmentioning
confidence: 88%
“…Galloway et al 1 See also http://burst.sci.monash.edu/sources and https://personal.sron.nl/ jeanz/bursterlist.html 2008; Kajava et al 2014, and references therein). Many bursting NSs in LXMBs alternate between so-called hard and soft spectral states (Muñoz-Darias et al 2014), and X-ray bursts can occur while the LMXB is in either of those two states or during state transitions (i.e. the intermediate state).…”
Section: Introductionmentioning
confidence: 99%
“…The neutron star spin frequency is measured to be about 363 Hz from X-ray burst oscillations (Strohmayer et al 1996). RXTE/PCA observations have shown that 4U 1728-34 undergoes the typical hysteresis pattern between hard and soft spectral states (e.g., Muñoz-Darias et al 2014). In the hard state the X-ray bursts are almost exclusively Eddingtonlimited photospheric radius expansion bursts (Galloway et al 2008;Zhang et al 2016), although the peak fluxes show a weak dependency with the properties of the persistent emission (Galloway et al 2003).…”
Section: Observations and Data Analysismentioning
confidence: 99%
“…Because the mass-to-radius ratio in neutron stars and black holes is similar 1 , the characteristic velocities and dynamical time scales near the compact object are also similar (v ∼ 0.5c, t < ∼ 1 ms). Thus, it is not surprising that BHXB and NSXB show very similar X-ray spectral and temporal characteristics (van der Klis 1994Klis , 2005Maccarone & Coppi 2003;Barret 2004;Di Salvo et al 2006;Muñoz-Darias et al 2014).…”
Section: Introductionmentioning
confidence: 99%